Forestry sector reform and distributional change of natural resource rent in Indonesia - Kato, G. (2005)
After the collapse of the centralized Soeharto regime, deforestation caused by over logging accelerated. To tackle this problem, an IMF/World Bank-led forestry sector reform program adopted a market-friendly approach involving the resumption of round wood exports and raising of the resource rent fee, with the aim to stop rent accumulation by plywood companies, which had enjoyed a supply of round wood at privileged prices. The Indonesian government, for its part, decentralized the forest concession management system to provide incentives for local governments and communities to carry out sustainable forest management. However, neither policy reform worked effectively. The round wood export ban was reimposed and the forest management system centralized again with cooperation from a newly funded industry led institution. In the midst of the confusion surrounding the policy reversal, the gap between the price of round wood in international and domestic markets failed to contract, although rent allocations to plywood industries were reduced during 1998 2003. The rents were not collected properly by the government, but accumulated unexpectedly in the hands of players in the black market for round wood.